Simultaneous copy number losses within multiple subtelomeric regions in early-onset type 2 diabetes mellitus. - Shinjiro Kodama; Tetsuya Yamada; Junta Imai; Shojiro Sawada; Kei Takahashi; Sohei Tsukita; Keizo Kaneko; Kenji Uno; Yasushi Ishigaki; Yoshitomo Oka; Hideki Katagiri (PLoS ONE)
Genetic factors play very important roles in the onset and progression of type 2 diabetes mellitus (T2DM). However, the genetic factors correlating with T2DM onset have not as yet been fully clarified. We previously found that copy number losses in the subtelomeric region on chromosome 4p16.3 were detected in early-onset Japanese T2DM patients (onset age <35 years) at a high frequency. Herein, we additionally found two novel copy number losses within the subtelomeric regions on chromosomes 16q24.2-3 and 22q13.31-33, which have significant associations with early-onset Japanese T2DM. The associations were statistically significant by Fisher's exact tests with P values of 5.19 × 10(-3) and 1.81 × 10(-3) and odds ratios of 5.7 and 4.4 for 16q24.2-3 and 22q13.31-33, respectively. Furthermore, copy number variation (CNV) analysis of the whole genome using the CNV BeadChip system verified simultaneous copy number losses in all three subtelomeric regions in 11 of our 100 T2DM subjects, while none of 100 non-diabetic controls showed the copy number losses in all three regions. Our results suggest that the mechanism underlying induction of CNVs is involved in the pathogenesis of early-onset T2DM. Thus, copy number losses within multiple subtelomeric regions are strongly associated with early-onset T2DM and examination of simultaneous CNVs in these three regions may lead to the development of an accurate and selective procedure for detecting genetic susceptibility to T2DM.